Al-Qalb al-Makānī fī al-Fiʿl al-Thulāthī al-Mahmūz (Dirāsah Binyawiyyah Maʿnawiyyah) - Ahmad Hidayatullah Zarkasyi; Habibul Muharam Sudarmawan (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
Al-qalb al-makānī (metathesis) is a linguistic phenomenon in Arabic involving the transposition of letters within a word. It is regarded as one of the mechanisms through which the Arabic language develops and forms part of the study of derivational morphology. Metathesis refers to the rearrangement of the letters of a lexical root while either preserving the original meaning or producing a functionally different one. In Arabic morphology, the triliteral root consists of three consonants conventionally represented as fāʾ, ʿayn, and lām, corresponding to the first, second, and third root letters. Metathesis may occur when the position of one root letter changes, as illustrated by word pairs such as laṭama–malaṭa, dhabaḥa–badhaḥa, and ghaḍiba–baghaḍa. In these examples, the second root letter in the first word becomes the third root letter in the second. Such changes may either preserve the original meaning or result in semantic variation. This article examines the phenomenon of metathesis in simple hamzated triliteral verbs recorded in Al-Munjid dictionary and provides a structural and semantic analysis of the forms in which this phenomenon occurs.